Methotrexate and prednisolone study in erythema nodosum leprosum (MaPs in ENL) protocol: a double-blind randomised clinical trial - Barbara de Barros, - (BMJ Publishing Group, 2021)
Introduction Erythema nodosum leprosum (ENL) is an immunological complication of leprosy. ENL results in morbidity and disability and if it is not treated can lead to death. The current treatment consists of thalidomide or high doses of oral corticosteroids for prolonged periods. Thalidomide is not available in many leprosy endemic countries. The use of corticosteroids is associated with morbidity and mortality. Identifying treatment regimens that reduce the use of corticosteroids in ENL is essential. Methotrexate (MTX) is used to treat many inflammatory diseases and has been used successfully to treat patients with ENL not controlled by other drugs, including prednisolone and thalidomide. We present the protocol of the ‘MTX and prednisolone study in ENL’ (MaPs in ENL) a randomised controlled trial (RCT) designed to test the efficacy of MTX in the management of ENL. Methods and analysis MaPs in ENL is an international multicentre RCT, which will be conducted in leprosy referral centres in Bangladesh, Brazil, Ethiopia, India, Indonesia and Nepal. Patients diagnosed with ENL who consent to participate will be randomly allocated to receive 48 weeks of weekly oral MTX plus 20 weeks of prednisolone or 48 weeks of placebo plus 20 weeks of prednisolone. Participants will be stratified by type of ENL into those with acute ENL and those with chronic and recurrent ENL. The primary objective is to determine whether MTX reduces the requirement for additional prednisolone. Patients’ reported outcome measures will be used to assess the efficacy of MTX. Participants will be closely monitored for adverse events. Ethics and dissemination Results will be submitted for publication in peer-reviewed journals. Ethical approval was obtained from the Observational/Interventions Research Ethics Committee of the London School of Hygiene & Tropical Medicine (15762); The Leprosy Mission International Bangladesh Institutional Research Board (in process); AHRI-ALERT Ethical Review Committee, Ethiopia; Ethics Committee of the Managing Committee of the Bombay Leprosy Project; and The Leprosy Mission Trust India Ethics Committee; the Nepal Health and Research Council and Health Research Ethics Committee Dr. Soetomo, Indonesia. This study is registered at www.clinicaltrials.gov. This is the first RCT of MTX for ENL and will contribute to the evidence for the management of ENL.